The Impact of Banditry, Kidnapping and Cost of Fuel on Food Security in Nigeria - Umar, Garpiya (Kashere Journal of Politics and International Relations, 2025)
Food security continues to be a critical issue in Nigeria, complicated by various challenges such as banditry, kidnapping, and rising fuel costs. This paper employs the Theory of Political Economy as a framework to understand the economic burden that households face due to increased food prices. These price hikes result from disrupted agricultural activities caused by banditry, kidnapping, and high fuel costs. Through a review of relevant literature and recent secondary data, this paper explores the impact of these factors on agricultural productivity and food availability, providing an analysis of the current state of food security in Nigeria. The Nigerian government has made significant efforts to reduce poverty, hunger, and food insecurity among its growing population. One notable initiative is the National Policy on Food and Nutrition, which aims to enhance Food and Nutrition Security (FNS) across various sectors and social groups. This policy has faced criticism for failing to bring about the necessary improvements in nutrition. Ongoing issues of banditry and kidnapping create insecurity, disrupting agricultural activities and preventing farmers from working their fields or safely transporting their goods. This disruption leads to decreased agricultural output and increased food prices. In addition, high fuel prices resulting from the removal of fuel subsidies in 2023 directly impact the cost of agricultural production and food transportation, making food less affordable for the population.